Analisis Penyebab Terjadinya Incident Process Berthing pada Tongkang BG. RMN 3316 Milik PT. Kartika Samudra Adijaya di Jetty PLTU Batang - Wesdhi Pandhu Putra; Maulidiah Rahmawati; Dyah Ratnaningsih (Universitas 45 Surabaya, 2024)
A ship accident is an unwanted event that can cause material losses or casualties. In this case, the party who feels aggrieved can file a lawsuit to get compensation for the losses suffered. It is undeniable that ship accidents often occur due to various reasons ranging from human error, technical factors, force majeur factors and several other factors. This research aims to find out what are the causes of berthing incidents and to find out the efforts made by ship owners after incidents that occurred at the jetty. In this thesis, a qualitative descriptive method is used with a fishbone diagram approach. Observations, interviews and literature studies are carried out to collect relevant data to identify and explain the causes that arise and also the consequences they cause, so that they can answer the formulation of the problem that has been determined. The results of the study concluded that the lack of communication between the crew and the jetty as well as unfavorable weather conditions were the main factors causing the incident. The lack of effective communication contributes to poor coordination during the berthing process. In an effort to handle the post-incident, PT. Kartika Samudra Adijaya formed an investigation team, increased crew training and strengthened cooperation with the jetty and port authorities. This research is expected to contribute to improving operational procedures and reducing the risk of similar incidents in the future.